Vapour Phase Methylation of Phenol Over Ni1-xMnxFe2O4 Type Ferrospinels - GUPTA, R.K.; PRASAD, R.; SINGH, SURANDER (Asian Journal of Chemistry, 2010)
Methylation of phenol with methanol has been studied over Ni1-xMnxFe2O4 (x = 0, 0.25, 0.5, 0.75, 1.0) type ferrospinels prepared via low temperature co-precipitation method. Alkylation of phenol in vapour phase leads to o-methylation of phenol yielding o-cresol and 2,6-xylenol as the major products. A maximum yield of 18.3 and 62.1 % were obtained for o-cresol and 2,6-xylenol, respectively with total ortho-selectivity ³ 97 % under optimized conditions of temperature 598 K, methanol/phenol ratio 6 and weight hour space velocity (WHSV) 0.5 h-1. Phenol conversion and selectivity for o-cresol and 2,6-xylenol depends on the acidicbasic properties of the catalysts. The selectivity for o-cresol was maximum when x = 0, whereas 2,6-xylenol selectivity increases as the value of x increases and become maximum when x = 1. The catalyst characterization was made by XRD, FTIR, NH3-TPD and BET-SA measurements.